Identification of Interactions of ABT-341 to Dipeptidyl Peptidase IV during Molecular Dynamics Simulations: Identikasi Interaksi-interaksi ABT-341 dengan Dipeptidil Peptidase IV pada Simulasi Dinamika Molekul - Istyastono, Enade; Gani, Michael (Universitas Tadulako, 2021)
Background: Dipeptidyl Peptidase IV (DPP-IV) is an established drug discovery target for type 2 diabetes mellitus (T2DM) therapy. On the other hand, molecular dynamics (MD) simulations have been widely employed to obtain insights of the protein-ligand interactions in structure-based drug design research projects. Moreover, a software to identify protein-ligand interactions called PyPLIF HIPPOS was made publicly available recently. Employing PyPLIF HIPPOS to identify the interactions of DPP-IV and its ligand ABT-341 during MD simulations was then of considerable interest. Objectives: The main aim of this study was to identify protein-ligand interactions of ABT-341 to DPP-IV during MD simulations. Material and Methods: The crystal structure of DPP-IV co-crystallized with ABT-341 obtained from the Protein Data Bank with code of 2I78 was used as the main material. YASARA-Structure was employed for performing 10 ns prodution run MD simulations with snapshots in every 100 ps and PyPLIF HIPPOS was used to identify the protein-ligand interactions. Results: There were 23 interactions involving 13 residues identified by employing PyPLIF HIPPOS during the MD simulations. Two of them identified in all snapshots, i.e., hydrophobic interactions to PHE357 and TYR666. Conclusions: PyPLIF HIPPOS was succesfully employed to identify the interactions of ABT-341 to DPP-IV during MD simulations.